2021
DOI: 10.1186/s40779-021-00356-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the immunoproteasome LMP2 ameliorates ischemia/hypoxia-induced blood–brain barrier injury through the Wnt/β-catenin signalling pathway

Abstract: Background Disruption of the blood–brain barrier (BBB) after a stroke can lead to brain injury and neurological impairment. Previous work confirmed the involvement of the immunoproteasome subunit of low molecular mass peptide 2 (LMP2) in the pathophysiology of ischemia stroke. However, the relationship between the immunoproteasome LMP2 and the BBB remains unclear. Methods Adult male Sprague–Dawley rats were subjected to transient middle cerebral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…Next, we explored the possibility that impaired transcription of Wnt/ ß -catenin target genes resulted from increased immunoproteasome activation, which is known to promote the destruction of ubiquitinated ß -catenin ( 34 ). We found that the immunoproteasome inhibitor (ONX) counteracts the downregulation of Wnt/ ß -catenin signaling pathway genes induced by Pb A-IE although this effect did not reach statistical significance in the case of the Axin2 gene ( Figures 3I–K ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we explored the possibility that impaired transcription of Wnt/ ß -catenin target genes resulted from increased immunoproteasome activation, which is known to promote the destruction of ubiquitinated ß -catenin ( 34 ). We found that the immunoproteasome inhibitor (ONX) counteracts the downregulation of Wnt/ ß -catenin signaling pathway genes induced by Pb A-IE although this effect did not reach statistical significance in the case of the Axin2 gene ( Figures 3I–K ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we explored the possibility that impaired transcription of Wnt/ ß -catenin target genes resulted from increased immunoproteasome activation, which is known to promote the destruction of ubiquitinated ß -catenin [27]. We found that the immunoproteasome inhibitor (ONX) counteracts the downregulation of Wnt/ ß -catenin signaling pathway genes induced by Pb A-IE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence was performed as described previously [ 22 ]. After blocking with 10% normal goat serum (Sigma-Aldrich, USA), slices were incubated with primary antibodies as following: rabbit anti-GFAP (1:300; Cell Signaling Technology, USA), rabbit anti-IBA1 (1:400; Abcam, Cambridge, MA, USA), rabbit anti-beta Amyloid (1:50; Abcam, Cambridge, MA, USA), and mouse anti-Olig1 (1:100; Santa Cruz, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 30 μg of total protein was loaded on an SDS–polyacrylamide gel as described previously [ 22 ]. The primary antibodies were used as follows: rabbit anti-myelin basic protein (MBP) and rabbit anti-IRAK1 (1:1000; Abcam, Cambridge, MA, USA), mouse anti-IL-6 (1:500; Abcam, Cambridge, MA, USA), mouse anti-Olig1 and mouse anti-TNF-a (1:300; Santa Cruz, USA), mouse monoclonal anti-β-actin (1:3000; Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%